PENGARUH KOMPETENSI PROFESIONAL DAN MODAL SOSIAL TERHADAP KINERJA DIMODERASI KEPEMIMPINAN TRANSFORMASIONAL (Studi pada Guru SD Kecamatan Doro kabupaten Pekalongan) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The aims of the study are to determine: the effect of professional competence toward teacher’s performance, the effect of social capital toward the teacher’s performance, the effect oftransformational leadership toward the teacher’s performance, Does transformational leadership moderates the effect of professional competence toward teacher performance, Does thetransformational leadership moderates the effect of social capital toward the elementary teachers’ performance throughout the District of Doro in Pekalongan regency. This research is conductedto the entire elementary school teacher in district Doro in Pekalongan Regency. This research takes 142 elementary teachers as the sample. The sample is chosen byusing Professional sampling. This research uses statistical techniques by doing the validation test, reliability test, normality test, classical assumptions, and test the feasibility of the modelBased on the survey results it is revealed that the professional competence gives significant and positive impact on teacher performance, social capital does not affect theperformance of teachers, leadership transformational gives positive and significant impact on teacher performance, leadership transformational does not moderate the influence of theprofessional competence of the teacher performance, and leadership transformational moderate the influence of social capital on teacher performance.Keywords: Professional Competence, Social Capital, transformational leadership and teacher performance.